Cooperation for climate adaptation in tourism - Romano Wyss (Revue de Géographie Alpine)
Climate change is an imminent challenge for many alpine tourism destinations. While the effects of changing climatic patterns are well documented with respect to the physical geographical sphere, research into the effects of climate change upon the regional socio-economic systems in the Alps is still rare. What is almost entirely missing is conceptual work identifying possible path-ways towards the implementation of adaptation measures with respect to climate change (see as one notable exception the contribution by Richard et al. 2010 in the last issue of the RGA). It is in this context that the paper at hand whishes to make a contribution by showing where the main barriers towards the successful implementation of adaptation measures lay. Theoretically, the paper builds upon distinct psychological and sociological concepts related to the actor-structure duality as suggested by structuration theory, while the Alps serve as the geographical frame of reasoning for the conceptual debate brought forward within the paper.